2019
DOI: 10.1002/marc.201800898
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Reconstituted Silk Microgels for the Storage and Release of Small Molecules

Abstract: Silk fibroin is a natural protein obtained from the Bombyx mori silkworm. In addition to being the key structural component in silkworm cocoons, it also has the propensity to self‐assemble in vitro into hierarchical structures with desirable properties such as high levels of mechanical strength and robustness. Furthermore, it is an appealing biopolymer due to its biocompatability, low immunogenicity, and lack of toxicity, making it a prime candidate for biomedical material applications. Here, it is demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 82 publications
(145 reference statements)
0
36
0
Order By: Relevance
“…Similarly, studies by Liu et al [59], developed polymeric nanoparticles containing poly(lactic-co-glycolic acid) (PLGA) to encapsulate the bioactive component curcumin and evaluate its antimicrobial capacity. It was observed that to have a significant reduction in E. coli viability required low concentrations of curcumin compared to the free bioactive and this was due to improved solubility and ability to direct curcumin bacteria.…”
Section: Antimicrobial Activity Of Nanoparticlesmentioning
confidence: 99%
“…Similarly, studies by Liu et al [59], developed polymeric nanoparticles containing poly(lactic-co-glycolic acid) (PLGA) to encapsulate the bioactive component curcumin and evaluate its antimicrobial capacity. It was observed that to have a significant reduction in E. coli viability required low concentrations of curcumin compared to the free bioactive and this was due to improved solubility and ability to direct curcumin bacteria.…”
Section: Antimicrobial Activity Of Nanoparticlesmentioning
confidence: 99%
“…Silks represent a distinctive group of structural protein that are degradable, biocompatible, eco‐friendly, and mechanically superior, and are proposed as promising biomedical materials . Various types of silk fibroin‐based materials, such as films, fibers, scaffolds, and gels, can be obtained through dissolving silk filaments and making regenerated silk fibroin (RSF) solutions . Physically crosslinked RSF hydrogels are often more brittle than the common chemically cross‐linked hydrogels.…”
mentioning
confidence: 99%
“…Microparticles were confined using a microfluidic trapping array. 33 First, the whole device was filled with buffer and all possible bubbles were erased. Next, microparticles in buffer were inserted into the device through the denoted inlet.…”
Section: Methodsmentioning
confidence: 99%